1998
DOI: 10.1016/s0370-2693(98)00852-1
|View full text |Cite
|
Sign up to set email alerts
|

Pfaffian solutions for the Manin-Radul-Mathieu SUSY KdV and SUSY sine-Gordon equations

Abstract: We reduce the vectorial binary Darboux transformation for the Manin-Radul supersymmetric KdV system in such a way that it preserves the Manin-Radul-Mathieu supersymmetric KdV equation reduction. Expressions in terms of bosonic Pfaffians are provided for transformed solutions and wave functions. We also consider the implications of these results for the supersymmetric sine-Gordon equation. q

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 11 publications
0
44
0
1
Order By: Relevance
“…A number of supersoliton and multi-supersoliton solutions were determined by a Crum-type transformation [19], [21], [25] and it was found that there exist infinitely many local conserved quantities. A connection was established between the super-Darboux transformations and super-Bäcklund transformations which allow for the construction of supersoliton solutions [11], [13], [16], [17], [20], [22], [24].…”
Section: Introductionmentioning
confidence: 99%
“…A number of supersoliton and multi-supersoliton solutions were determined by a Crum-type transformation [19], [21], [25] and it was found that there exist infinitely many local conserved quantities. A connection was established between the super-Darboux transformations and super-Bäcklund transformations which allow for the construction of supersoliton solutions [11], [13], [16], [17], [20], [22], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent development on SUSY integrable systems, especially on Bäcklund and Darboux transformations, allowed a better understanding and the construction of soliton solutions. For examples, Liu and Mañas [16,17] provided the N-Darboux transformation for the Manin-Radul(-Mathieu) SUSY Korteweg-de Vries (KdV) system, which can also be applied to the SUSY sine-Gordon equaiton, using Pfaffian solutions. In addition, Xue et al [18] investigated the Bäcklund transformation of the SUSY sine-Gordon equation as a nonlinear superposition formula and they were able to link it with the SUSY MKdV equations.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed idea of constructing complexitons through special determinants, for example, the Wronskian and Casorati determinants, will also work for other integrable equations. In particular, super-complexitons can be similarly generated for super integrable equations, which will extend the theory of supersolitons [ 11,12].…”
Section: Wx Mamentioning
confidence: 99%
“…The Casoratian technique [ 17] is one of the ways to solve the bilinear Toda lattice equation (12). The corresponding solutions to the bilinear Toda lattice equation (12) are determined by the Casorati determinant:…”
Section: Toda Lattice Equationmentioning
confidence: 99%